2015
DOI: 10.1103/physrevb.92.134107
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a Ni-Ti interatomic potential with high predictive accuracy of the martensitic phase transition

Abstract: Phase transitions in nickel-titanium shape-memory alloys are investigated by means of atomistic simulations. A second nearest-neighbor modified embedded-atom method interatomic potential for the binary nickel-titanium system is determined by improving the unary descriptions of pure nickel and pure titanium, especially regarding the physical properties at finite temperatures. The resulting potential reproduces accurately the hexagonal-close-packed to body-centered-cubic phase transition in Ti and the martensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
160
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 83 publications
12
160
0
1
Order By: Relevance
“…Additionally, it is evident that the average width of twin is in nanometer magnitude, which agrees well with experimental data [32]. However, it must be pointed out that the size effect on the transformation temperatures and the nanotwin formations disappears when the specimen is sufficiently large [21]. Figure 6 illustrates a resultant stress-strain response of the pillar subjected to longitudinal compressive deformations at 450 K. In this figure, the phase transition onset in loading/unloading is represented by an arrow.…”
Section: Simulationssupporting
confidence: 78%
See 2 more Smart Citations
“…Additionally, it is evident that the average width of twin is in nanometer magnitude, which agrees well with experimental data [32]. However, it must be pointed out that the size effect on the transformation temperatures and the nanotwin formations disappears when the specimen is sufficiently large [21]. Figure 6 illustrates a resultant stress-strain response of the pillar subjected to longitudinal compressive deformations at 450 K. In this figure, the phase transition onset in loading/unloading is represented by an arrow.…”
Section: Simulationssupporting
confidence: 78%
“…Comparatively speaking, MEAM potentials are well suited for simulations of multicomponent systems composed of elements with different ground states, because they allow for characterizing a wide range of phases (fcc, bcc, hcp, diamondstructured, and even gases) using a common mathematical function [28]. However, Ko et al [21] strongly recommended the use of second nearest-neighbor modified embeddedatom method (2NN MEAM) when choosing an interatomic potential in the NiTi binary alloy. Furthermore, a comparison of the predicted results with the experimental ones [3] indicated that such a model could be available for representing the characteristics of the low temperature martensitic structure (B19 ).…”
Section: Nn Meam Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercell equilibrium volumes are taken from experiments [24]. CMD simulations are performed using LAMMPS [25], describing the Ti-Ti interactions via the second-nearest-neighbor modified embedded-atom method (MEAM) [26], as parameterized in [27], and integrating the equations of motion at 1-fs timesteps. The equilibrium volumes of supercells formed of 14×14×14 conventional bcc cells (5488 Ti atoms) are determined as a function of temperature via NPT sampling based on the Parrinello-Rahman barostat [28] and the Langevin thermostat.…”
mentioning
confidence: 99%
“…The periodic boundary conditions are applied along the three orthogonal directions x, y and z of the cells. Atomic interactions in the Ni-Ti system are described by the modified embedded-atom method potential developed by Ko et al [24]. This interatomic potential can quite accurately predict the temperature-and stress-induced MT in NiTi alloys [24 -26].…”
Section: Modelingmentioning
confidence: 99%